The Binomial Theorem
edit
Before we discuss the binomial theorem, we need to discuss combinations. In order to discuss combinations, we need to discuss factorials.
The factorial of a number is the product of all numbers from 1 to that number. It is represented by the symbol
!
{\displaystyle !}
after the number.
e.g.
4
!
=
4
×
3
×
2
×
1
=
24
{\displaystyle 4!=4\times 3\times 2\times 1=24}
The factorial can be formally defined as:
n
!
=
{
1
,
if
n
=
0
n
×
(
n
−
1
)
!
,
otherwise
{\displaystyle n!={\begin{cases}1,&{\text{if }}n=0\\n\times (n-1)!,&{\text{otherwise}}\end{cases}}}
10 3-item combinations can be chosen from a set of 5. Thus, 5C3 = 10.
Combinations are a way of calculating how many ways a set of items with a given size can be selected from a larger set of items. It is typically represented either by the column notation
(
n
k
)
{\displaystyle {\binom {n}{k}}}
or by the notation
n
C
k
{\displaystyle nCk}
.
Combinations can be calculated using factorials:
(
n
k
)
=
n
!
k
!
(
n
−
k
)
!
,
n
≥
k
{\displaystyle {\binom {n}{k}}={\frac {n!}{k!(n-k)!}},n\geq k}
.
e.g.
(
5
3
)
=
5
!
3
!
2
!
=
120
6
(
2
)
=
120
12
=
10
{\displaystyle {\binom {5}{3}}={\frac {5!}{3!2!}}={\frac {120}{6(2)}}={\frac {120}{12}}=10}
The Binomial Theorem
edit
The binomial theorem is used when we need to raise a binomial, an expression consisting of two terms, to the power of a given
n
{\displaystyle n}
, e.g.
(
x
+
2
)
3
{\displaystyle (x+2)^{3}}
.
The binomial theorem states that
(
a
+
b
)
n
=
(
n
0
)
a
n
+
(
n
1
)
a
n
−
1
b
+
(
n
2
)
a
n
−
2
b
2
+
⋯
+
(
n
n
)
b
n
{\displaystyle (a+b)^{n}={\binom {n}{0}}a^{n}+{\binom {n}{1}}a^{n-1}b+{\binom {n}{2}}a^{n-2}b^{2}+\dots +{\binom {n}{n}}b^{n}}
e.g.
(
x
+
2
)
3
=
(
3
0
)
x
3
+
(
3
1
)
x
2
(
2
)
+
(
3
2
)
x
(
2
2
)
+
(
3
3
)
(
2
3
)
=
(
1
)
x
3
+
(
3
)
(
2
)
x
2
+
(
3
)
(
4
)
x
+
(
1
)
(
8
)
=
x
3
+
6
x
2
+
12
x
+
8
{\displaystyle {\begin{aligned}(x+2)^{3}&={\binom {3}{0}}x^{3}+{\binom {3}{1}}x^{2}(2)+{\binom {3}{2}}x(2^{2})+{\binom {3}{3}}(2^{3})\\&=(1)x^{3}+(3)(2)x^{2}+(3)(4)x+(1)(8)\\&=x^{3}+6x^{2}+12x+8\end{aligned}}}
The binomial theorem is sometimes summarised as
(
a
+
b
)
n
=
∑
k
=
0
n
(
n
k
)
a
n
−
k
b
k
{\displaystyle (a+b)^{n}=\sum _{k=0}^{n}{\binom {n}{k}}a^{n-k}b^{k}}
Arithmetic Progressions
edit
An arithmetic sequence is a progression in which the numbers increment by a fixed quantity from one term to the next.
e.g.
6
,
8
,
10
,
12
,
14
,
…
{\displaystyle 6,8,10,12,14,\dots }
is an arithmetic sequence (the fixed quantity is
2
{\displaystyle 2}
)
The nth term of an arithmetic sequence can be determined using
a
n
=
a
1
+
(
n
−
1
)
d
{\displaystyle a_{n}=a_{1}+(n-1)d}
where
a
n
{\displaystyle a_{n}}
is the nth term,
a
1
{\displaystyle a_{1}}
is the first term, and
d
{\displaystyle d}
is the difference between two consecutive terms in the progression.
A visual proof for how the sum of an arithmetic sequence can be found
e.g. The sequence
4
,
7
,
10
,
13
,
…
{\displaystyle 4,7,10,13,\dots }
has a difference of
7
−
4
=
3
{\displaystyle 7-4=3}
. So the nth term of this sequence can be determined by
a
n
=
4
+
3
(
n
−
1
)
=
4
+
3
n
−
3
=
1
+
3
n
{\displaystyle a_{n}=4+3(n-1)=4+3n-3=1+3n}
. Thus, if we wanted to find the 1000th term of the progression, we can use the nth term formula:
a
1000
=
1
+
3
(
1000
)
=
3001
{\displaystyle a_{1000}=1+3(1000)=3001}
.
Sum of the first n terms
edit
The sum of the first n terms of an arithmetic progression can be found using the formula:
S
n
=
n
(
a
1
+
a
n
)
2
{\displaystyle S_{n}={\frac {n(a_{1}+a_{n})}{2}}}
e.g. Find the sum of the first 50 terms of the sequence
23
,
27
,
31
,
35
,
…
{\displaystyle 23,27,31,35,\dots }
d
=
27
−
23
=
4
a
1
=
23
a
50
=
23
+
(
50
−
1
)
(
4
)
=
23
+
49
(
4
)
=
23
+
196
=
219
S
50
=
50
(
23
+
219
)
2
=
25
(
242
)
=
6050
{\displaystyle {\begin{aligned}d&=27-23=4\\a_{1}&=23\\a_{50}&=23+(50-1)(4)=23+49(4)=23+196=219\\S_{50}&={\frac {50(23+219)}{2}}=25(242)=6050\end{aligned}}}
Geometric Progressions
edit
A geometric progression is like an arithmetic progression except that instead of adding a constant from one term to the next, we multiply each term by a constant to get the next term.
e.g.
3
,
6
,
12
,
24
,
48
,
…
{\displaystyle 3,6,12,24,48,\dots }
is a geometric sequence.
The nth term for a geometric progression is given by
a
n
=
a
1
r
n
−
1
{\displaystyle a_{n}=a_{1}r^{n-1}}
where
a
n
{\displaystyle a_{n}}
is the nth term,
a
1
{\displaystyle a_{1}}
is the first term, and
r
{\displaystyle r}
is the ratio between two consecutive terms.
Sum of the first n terms
edit
Proof without words of the formula for the sum of a geometric series – if |r | < 1 and n → ∞, the r n term vanishes, leaving S ∞ = a / 1 − r
The sum of the first n terms of a geometric series can be found using
a
(
1
−
r
n
)
1
−
r
{\displaystyle {\frac {a(1-r^{n})}{1-r}}}
.
e.g. The sum of the first 10 terms of the sequence
3
,
6
,
12
,
24
,
48
,
…
{\displaystyle 3,6,12,24,48,\dots }
is
3
(
1
−
2
10
)
1
−
2
=
3
(
−
1023
)
−
1
=
3
(
1023
)
=
3069
{\displaystyle {\frac {3(1-2^{10})}{1-2}}={\frac {3(-1023)}{-1}}=3(1023)=3069}
.
A convergent geometric progression is one where the terms get smaller and smaller, meaning that as
n
{\displaystyle n}
approaches infinity, the
n
{\displaystyle n}
th term approaches zero. An important consequence of this is that the progression will have a defined sum to infinity.
We can tell if a sequence is convergent if the ratio
r
{\displaystyle r}
is less than
1
{\displaystyle 1}
and more than
−
1
{\displaystyle -1}
. If this condition is not satisfied, the sequence is divergent .
The sum to infinity of a geometric progression is the value that the sum of the first
n
{\displaystyle n}
terms as
n
{\displaystyle n}
approaches infinity. If a progression is convergent, its sum to infinity will be finite.
The sum to infinity is given by
S
∞
=
a
(
1
−
r
∞
)
1
−
r
{\displaystyle S_{\infty }={\frac {a(1-r^{\infty })}{1-r}}}
which is equivalent to
S
∞
=
a
1
−
r
{\displaystyle S_{\infty }={\frac {a}{1-r}}}
if
−
1
<
r
<
1
{\displaystyle -1<r<1}
.
e.g. The sum to infinity of the sequence
1
,
1
2
,
1
4
,
1
8
,
…
{\displaystyle 1,{\frac {1}{2}},{\frac {1}{4}},{\frac {1}{8}},\dots }
is
1
1
−
1
2
=
1
1
2
=
2
{\displaystyle {\frac {1}{1-{\tfrac {1}{2}}}}={\frac {1}{\tfrac {1}{2}}}=2}
← Trigonometry · Differentiation →